Phosphorus adsorption by a latossol from the state of Minas Gerais, Brasil - Mansano, Aírton; Polli, Helvécio de; Freire, Jesiel C.; Sobral, Lafayette F.; Souza, Maurício de; Ventorin, Nelson; Mello, Francisco de A. F. de (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1976)
It: was studied the adsorption of R by samples of the horizons A1 (0-22cm), A3 (22-56cm) and B22 (155-200cm) of a Latossol f rom the State of Minas Gerais, Brasil, by mean of the isotherm of Langmuir. The maximum adsorption values (b) and selectivity constant (K) calculated from the linear pattern of the Langmuir equation were correlated with some physical and chemical: characteristics of the horizons. The main conclusion were as follows: a) The adsorption isotherm showed two definite regions: the one regarding to the high R fixation is in accordance with the Langmuir equation. b) It was observed big differences in respect to the values of maximum adsorption (b) as well as to the selectivity constant (K) .